2017
DOI: 10.1021/jacs.7b07808
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)/NO(g) Reductive Coupling Producing a trans-Hyponitrite Bridged Dicopper(II) Complex: Redox Reversal Giving Copper(I)/NO(g) Disproportionation

Abstract: A copper complex, [CuI(tmpa)(MeCN)]+, effectively reductively couples NO(g) at RT in methanol (MeOH), giving a structurally characterized hyponitrito-dicopper( II) adduct. Hydrogen-bonding from MeOH is critical for the hyponitrite complex formation and stabilization. This complex exhibits the reverse redox process in aprotic solvents, giving CuI + NO(g), leading to CuI-mediated NO(g)-disproportionation. The relationship of this chemistry to biological iron and/or copper mediated NO(g) reductive coupling to giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(91 citation statements)
references
References 51 publications
(55 reference statements)
6
85
0
Order By: Relevance
“…The stability of the title compounds was not in line with the usual classification of the hydrogenhyponitrite ion as an intermediate towards nitrous-oxide formation. [12,18,19,30] However,a closer look at space-filling modelso f5-7 showed that the phenylg roups of the bisphosphanel igands enclosed the hydrogenhyponitrite/hyponitrite ligand and the ruthenium(II) center ( Figure 13).…”
Section: Differencementioning
confidence: 99%
See 2 more Smart Citations
“…The stability of the title compounds was not in line with the usual classification of the hydrogenhyponitrite ion as an intermediate towards nitrous-oxide formation. [12,18,19,30] However,a closer look at space-filling modelso f5-7 showed that the phenylg roups of the bisphosphanel igands enclosed the hydrogenhyponitrite/hyponitrite ligand and the ruthenium(II) center ( Figure 13).…”
Section: Differencementioning
confidence: 99%
“…[13,17] Cobalt, copper,i ron, ruthenium,a nd yttrium form polynuclear cis-a nd trans-hyponitrito complexes. [12,[14][15][16][18][19][20] There is only one type of coordinated hydrogenhyponitrite known.B çttchere tal. synthesized ad iruthenium(I) complex, bridged with sterically demanding phosphide ligands, which is capable of reducing nitric oxide to ab ridging hyponitrite ligand according to [Ru 2 (CO) 4 (m-dppm)(m-H)(m-PtBu 2 )] + 2NO!…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide (NO) reduction, known as the process of relieving nitrosative stress for pathogenic bacteria and fungi, is central to the regulation of NO x levels . Biomimetic model studies suggest that NO reduction yielding N 2 O may occur via hyponitrite [N 2 O 2 ] 2− ‐bound intermediate, generated by inter−/intra‐molecular (O)N–N(O) coupling reaction of two reduced metal‐NO units ({Fe(NO)} 7/8 ) or coupling of metal‐[NO] 2− unit with exogenous NO gas . It was demonstrated that NO ligands bound to Fe in mononuclear dinitrosyl iron complexes, existing in cells as intrinsic NO‐storage/−transport species in the biological systems, do not voluntarily form a reductive coupling product (hyponitrite), due to their spin‐parallel electronic structure of two NO‐coordinated ligands in [Fe(NO) 2 ] unit .…”
Section: Discussionmentioning
confidence: 99%
“…This result demonstrates that H‐bonding interactions are required to stabilize N‐N bond of hyponitrite. Furthermore, Karlin et al proposed that the hyponitrite – bridged dicopper complex [{Cu(tmpa)} 2 ( μ ‐N 2 O 2 )] 2+ was generated by introducing exogenous NO to [Cu(tmpa)(MeCN)](B[C 6 F 5 ] 4 ) in methanol at room temperature, as shown in Scheme . However, replacing reaction solution with THF results in NO disproportionation to yield Cu ‐ nitrito complex [{Cu(tmpa)} 2 (NO 2 )] + accompanied by release of N 2 O.…”
Section: Metal‐hyponitrite Complexes Stabilized By Hydrogen Bondingmentioning
confidence: 99%